2021
DOI: 10.3389/fonc.2021.749682
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Anlotinib Reverses Nivolumab Resistance in Advanced Primary Pulmonary Lymphoepithelioma-Like Carcinoma With FGFR3 Gene Amplification

Abstract: BackgroundPrimary pulmonary lymphoepithelioma-like carcinoma (LELC) is a rare type of non-small cell lung cancer (NSCLC). Currently, anti-programmed death-1 (PD-1)/programmed death ligand-1 (PD-L1) has become an important treatment for NSCLC. Anti-human PD-1 monoclonal antibodies, such as nivolumab, significantly prolong the survival time of patients with advanced lung adenocarcinoma and lung squamous cell carcinoma. However, there are few reports on the therapeutic effect, drug resistance mechanism, and strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Antivascular targeted therapy is currently one of the important modalities in the treatment of malignant tumors and has shown good therapeutic effects on lung and intestinal cancers. Available data suggest that there is a synergistic effect of antivascular targeted therapy and immunotherapy [ 52 55 ], and some studies suggest that antivascular targeted therapy can reverse PD-1 resistance to some extent [ 56 ]. Retrospective data analysis suggests that antivascular targeted therapy has also shown good disease control rates in patients with specific tumors after organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Antivascular targeted therapy is currently one of the important modalities in the treatment of malignant tumors and has shown good therapeutic effects on lung and intestinal cancers. Available data suggest that there is a synergistic effect of antivascular targeted therapy and immunotherapy [ 52 55 ], and some studies suggest that antivascular targeted therapy can reverse PD-1 resistance to some extent [ 56 ]. Retrospective data analysis suggests that antivascular targeted therapy has also shown good disease control rates in patients with specific tumors after organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Xu's published work in World Journal of Surgical Oncology presented a case of lung adenocarcinoma with HER2 p. Asp769Tyr mutation that was successfully treated with a combination of afatinib and anlotinib. 163,[180][181][182] Lorlatinib is a targeted therapy drug employed for the treatment of non-small cell lung cancer (NSCLC), acting as a small molecule tyrosine kinase inhibitor. Lorlatinib functions by suppressing the activity of anaplastic lymphoma kinase (ALK), c-ros oncogene 1 (ROS1), and proto-oncogene tyrosine-protein kinase (RET).…”
Section: -110mentioning
confidence: 99%
“…Preclinical researches and case reports demonstrated that anlotinib may modulate the tumor microenvironment and act synergistically with immune checkpoint inhibitors. [11][12][13][14][15][16][17] Current studies have shown encouraging efficacy of the clinical use of anlotinib combination therapy, and a case reported first-line pemetrexed and carboplatin plus anlotinib achieved CR. [18][19][20][21][22] However, the sample size of current studies is small and more studies are still needed to confirm the efficacy and safety of anlotinib combination therapy in different patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%